Deciphering excited state properties utilizing algebraic diagrammatic construction schemes of decreasing order. Issue 11 (17th February 2021) - Hoffmann, Marvin; Dreuw, Andreas
Abstract: Excited state properties are difficult to trace back to the common molecular orbital picture when the excited state wavefunction is a linear combination of two or more Slater determinants. Here, a theoretical methodology is introduced based on the algebraic diagrammatic construction scheme for the polarization propagator (ADC( n )) that allows to make this connection and to eventually derive structure–function relationships. The usefulness of this approach is demonstrated by an analysis of the transition dipole moments of the low‐lying 1 B 3 u and 2 B 3 u states of anthracene and (1, 4, 5, 8)‐tetraazaanthracene. Abstract : Analysis of ADC schemes for the polarization propagator with decreasing order of perturbation theory yields detailed insight into the origins of specific excited state properties of multi‐determinantial wavefunctions. Tracing them down to the molecular orbital picture opens the path to structure–property relationships and rational design of molecules with tailored optical properties.